2012
DOI: 10.4162/nrp.2012.6.3.213
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of nutrient intake and diet quality of gastric cancer patients in Korea

Abstract: This study was conducted to identify dietary factors that may affect the occurrence of gastric cancer in Koreans. Preoperative daily nutrition intake and diet quality of patients diagnosed with gastric cancer were evaluated. Collected data were comparatively analyzed by gender. The results were then used to prepare basic materials to aid in the creation of a desirable postoperative nutrition management program. The subjects of this study were 812 patients (562 men and 250 women) who were diagnosed with gastric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 20 publications
2
18
1
Order By: Relevance
“…In a similar study by Lim et al in Korea (17), as in our study, a higher INQ of vitamin A was observed in GC patients compared to the controls. In contrast, the opposite was observed in case of vitamin B6 (17).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…In a similar study by Lim et al in Korea (17), as in our study, a higher INQ of vitamin A was observed in GC patients compared to the controls. In contrast, the opposite was observed in case of vitamin B6 (17).…”
Section: Discussionsupporting
confidence: 91%
“…The number of nutrients and the nutrient standards used for analysis are flexible parameters which may be varied for each clinical situation. Illustrative examples include INQ analysis of simple foods, an institutional house diet, the diabetic exchange list, and the diagnostic evaluation of the dietary intake of a hospitalized patient (17).…”
Section: Assessment Of Inqmentioning
confidence: 99%
See 3 more Smart Citations